THE COMMUNICATION PATTERN IN THE COOPERATION RELATIONSHIP BETWEEN ANTV TELEVISION STATION AND KOMANDO PRODUCTION HOUSE AT PESBUKERS PROGRAM - ., Muslim (UNIVERSITAS PAKUAN, 2020)
The purpose of this research is to know the communication pattern in the cooperation relationship between ANTV television station and KOmando production house at Pesbukers program and to know the production process done by cooperation between ANTV television station with KOmando production house (pra-production, production, until post-production) on the Pesbukers program, as well as to find out what problems will occur in the cooperation relationship between ANTV television station and KOmando production house on Pesbukers program. This research uses a qualitative research approach, because this research requires field observation and also researchers conducted interviews with the sources related to this research to obtain valid data. This research uses relationship theory, known by the name Palo Alto Group according to Stephen W. Littejohn [4]. ANTV joined with KOmando production so that cooperate and form a relationship as